Black Acting Methods - Luckett, Sharrell; Shaffer, Tia M. (Taylor & Francis, 2016)
Black Acting Methods seeks to offer alternatives to the Euro-American performance styles that many actors find themselves working with.　 A wealth of contributions from directors, scholars and actor trainers address afrocentric processes and aesthetics, and interviews with key figures in Black American theatre illuminate their methods. This ground-breaking collection is an essential resource for teachers, students, actors and directors seeking to reclaim, reaffirm or even redefine the role and contributions of Black culture in theatre arts.